2009
DOI: 10.1159/000226604
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends in the Epidemiology of Neonatal Sepsis and Antibiotic Susceptibility of Causative Agents

Abstract: Background: In an era with increased maternal antibiotic use, patterns in early- and late-onset sepsis and antibiotic susceptibility may have changed. Objectives: To identify longitudinal trends in causative microorganisms for neonatal sepsis and analyze antibiotic susceptibility of all blood isolates of infants with sepsis. Methods: Early- and late-onset sepsis cases from 29 years (1978–2006) were studied retrospectively, in five clusters of 5 years (period I–V) and one cluster of 4 years (period VI), includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
102
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(121 citation statements)
references
References 56 publications
12
102
1
6
Order By: Relevance
“…The rates of sepsis in this study are comparable to those in units in Taiwan that reported rates ranging from 3% to 4% [18,19], but lower compared with data from other countries such as the Philippines, The Netherlands, and Nigeria, where sepsis rates have been reported to range from 15.1% to 19.6% [20][21][22]. Furthermore, at 2.68 cases per 1,000 live births, the rate of sepsis for inborn infants was lower than that reported in other countries including Korea (5.9 cases per 1,000 live births) [23], the USA (6.1 cases per 1,000 live births) [4], and India (14.8 cases per 1,000 live births) [24].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The rates of sepsis in this study are comparable to those in units in Taiwan that reported rates ranging from 3% to 4% [18,19], but lower compared with data from other countries such as the Philippines, The Netherlands, and Nigeria, where sepsis rates have been reported to range from 15.1% to 19.6% [20][21][22]. Furthermore, at 2.68 cases per 1,000 live births, the rate of sepsis for inborn infants was lower than that reported in other countries including Korea (5.9 cases per 1,000 live births) [23], the USA (6.1 cases per 1,000 live births) [4], and India (14.8 cases per 1,000 live births) [24].…”
Section: Discussionsupporting
confidence: 75%
“…In the USA, the overall cumulative incidence of EOS is from 0.8 to 1.0 cases per 1,000 live births [9] and the rate of LOS is 36% in preterm infants (22)(23)(24)(25)(26)(27)(28) weeks gestational age/401-1500 g birth weight) [10]. Similarly, two studies of groups of neonatal intensive care unit (NICUs) in developing countries including Malaysia, Thailand, China, and India, found the rate of EOS to be from 0.62 to 0.72 cases per 1,000 live births [11,12].…”
Section: Brief Communication (Original)mentioning
confidence: 99%
“…2 Neonatal septicaemia can be categorised as earlyonset neonatal sepsis, representing maternally derived infections; and late-onset neonatal sepsis, representing hospital-acquired infection. 3,4 Knowledge of the local epidemiology of neonatal sepsis assists clinicians and infection control programmes to prioritise interventions for prevention of neonatal sepsis-related morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Esto se ha facilitado por el uso prolongado de antimicrobianos sin la suspensión precoz luego de no comprobarse la presencia de infección, ya sea, por la ausencia de síntomas clínicos y/o hemocultivos negativos, provocando el aumento de las tasas de infecciones por microorganismos resistentes y gramnegativos. Se ha demostrado adicionalmente, que vancomicina es uno de los principales antimicrobianos que favorecen el aumento de las tasas de infecciones por candidas en una UCIN, lo que constituye un grave y emergente problema en las UCIN en el mundo con aumento significativo de la morbi-mortalidad 28 . La aparición de microorganismos resistentes a vancomicina, como Enterococcus y S. aureus constituye un problema agregado al ya expuesto, dado que pueden causar infecciones graves, potencialmente mortales, con opciones terapéuticas limitadas y de alto costo, ocasionando importantes impactos en la salud pública.…”
Section: Por Selección De Infecciones Con Otros Microorganismos Y/o Runclassified